PERILAKU KONSUMSI PANGAN SUMBER KARBOHIDRAT RUMAHTANGGA PETANI KELAPA SAWIT DI KECAMATAN KANDIS KABUPATEN SIAK - Heriyanto Heriyanto (Universitas Lancang Kuning, 2016)
This research generally aims to analyze the behavior of food consumption source of carbohydrate, specifically, this study aims to analyze the dominant factor and analyze the response of food consumption expenditure dominant source of carbohydrate for factors that influence it. To answer this research purpose built models Almost Ideal Demand System (AIDS) were analyzed by methods Seemingly Unreleated Regression (SUR).Food commodities sources of carbohydrates are included in the model to include five commodities (commodity groups), include: rice, yam, noodles, cassava and potatoes. The results showed that the higher the income level, the proportion of food expenditure of commodities as rice, yam, noodles, cassava, and potatoes tend to increase. Meanwhile, the higher the mother's education the more domestic rice consumption, while consumption of yam noodles, cassava and potatoes tend to decline. The analysis showed that the price elasticity of its own for the entire commodity observed negative sign except cassava and yams and potatoes only the value of elasticity is greater than one. This indicates that the commodity consumption expenditures yams and potatoes are responsive to changes in its price. Similarly, the cross-price elasticities show the value of elasticity (in absolute value) with cassava yams and potatoes is greater than one, means commodity consumption expenditures yams are responsive to changes in prices of other commodities. Meanwhile, the income elasticity shows two commodities that have an income elasticity greater than one, which is the income elasticity for commodities noodles, and cassava. From these findings it can be stated that the policies related to revenue-raising efforts should be made to boost household consumption, especially consumption of palm oil farmers noodles and cassava, while the price control policy needs to be done to increase the consumption of yams.